2023
DOI: 10.1039/d2ob02257e
|View full text |Cite
|
Sign up to set email alerts
|

Profiling rhythmicity of bile salt hydrolase activity in the gut lumen with a rapid fluorescence assay

Abstract: Diurnal rhythmicity of cellular function is key to survival for most organisms on earth. Many circadian functions are driven by the brain, but regulation of a separate set of peripheral...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 63 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…Our findings appear to be consistent with a report that four days of simulated shift work dampens insulin sensitivity, a marker of risk for metabolic disease, which may be mediated by internal desynchronization between circadian- and behavior-driven rhythms like that found in our study. Data from experiments focused specifically on meal timing suggest a specific role for the prior schedule of food intake in our study, potentially mediated by shifted circadian rhythmicity in functional enzymatic activity of the gut microbiome …”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our findings appear to be consistent with a report that four days of simulated shift work dampens insulin sensitivity, a marker of risk for metabolic disease, which may be mediated by internal desynchronization between circadian- and behavior-driven rhythms like that found in our study. Data from experiments focused specifically on meal timing suggest a specific role for the prior schedule of food intake in our study, potentially mediated by shifted circadian rhythmicity in functional enzymatic activity of the gut microbiome …”
Section: Discussionmentioning
confidence: 86%
“…Data from experiments focused specifically on meal timing 42 suggest a specific role for the prior schedule of food intake in our study, potentially mediated by shifted circadian rhythmicity in functional enzymatic activity of the gut microbiome. 43 Indeed, recent studies have shown that the temporal pattern of food intake during the prior shift days may serve as a peripheral clock source. 2,42 In our study, food intake was equally distributed across the 24 h of the constant routine when the blood samples were taken but was shifted to the night in the prior simulated night shift days, thus providing a shifted peripheral clock signal.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Using this cholic acid-based ABP, we profiled BSH activities within gut microbes and identified active BSH enzymes within healthy and colitic mouse gut microbiomes. Additional approaches have been developed using chemical probes containing a fluorogenic or luminogenic group to monitor BSH activity (Brandvold et al, 2019; Khodakivskyi et al, 2021; Kombala et al, 2023; Sveistyte et al, 2020), alternative covalent warheads to profile and inhibit BSH activity (Adhikari et al, 2020; Brandvold et al, 2021), and photoaffinity labels to identify bile acid-binding proteins (Forster et al, 2022; Liu et al, 2022; Yang et al, 2022, 2023; Zhuang et al, 2017). Despite the number of emerging chemical tools to study BSH activities, the substrate preferences within the BSH family at a metaproteome level remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Luminogenic and fluorogenic probes have been developed to detect BSH activity that comprise luciferin or quenched fluorophore bile acid conjugates, respectively, in which the imaging agent is activated upon bile acid deconjugation. [22][23][24][25] However, these approaches are not able to distinguish between BSH activities or substrate preferences from different bacteria in a complex sample.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the increasingly recognized importance of BSH in human health and disease, chemical tools to image their activities and probe their functions within the gut microbiome have recently begun to emerge. Luminogenic and fluorogenic probes have been developed to detect BSH activity that comprise luciferin or quenched fluorophore bile acid conjugates, respectively, in which the imaging agent is activated upon bile acid deconjugation [22–25] . However, these approaches are not able to distinguish between BSH activities or substrate preferences from different bacteria in a complex sample.…”
Section: Introductionmentioning
confidence: 99%